THE EFFECT OF TE (TIME ECHO) VARIATIONS ON DIAGNOSTIC ACCURACY OF MAGNETIC RESONANCE SPECTROSCOPY FOR SPACE OCCUPYING LESION - Hanna Adkhilah (Wealth Community Empowerment, 2025)
Magnetic Resonance Spectroscopy (MRS) is an advanced radiology technique used to analyze brain metabolites, particularly in the diagnosis of abnormalities such as Space Occupying Lesion (SOL). Variations in parameters, such as Time Echo (TE), can affect the resulting spectrum, making it important to understand their impact. This study aims to analyze the effect of TE variations on MRS spectrum results in patients with SOL through a literature review. The methodology used is a literature review, collecting and analyzing various previous studies that discuss the impact of TE variations in MRS examinations. Data sources are taken from scientific journals, articles, and books relevant to the research topic. The literature review shows that TE variations, both short TE and long TE, have a significant impact on signal intensity and the types of metabolites detected in the MRS spectrum. These results indicate that the appropriate selection of TE can enhance diagnostic accuracy in detecting SOL. Data analysis shows significant differences in the Area Under Curve (AUC) values of the metabolites NAA, Creatine, Choline, Lactate, and myo-Inositol between different TE usages. These findings indicate that TE variations affect signal intensity and the types of metabolites detected in the MRS spectrum. Time Echo variations have a significant effect on MRS spectrum results in patients with SOL, which can improve diagnostic accuracy and understanding of MRS techniques in clinical practice. These findings are expected to serve as a reference for the development of knowledge in the field of radiology.